Application of plasma-activated water for Escherichia coli decontamination and shelf-life extension of kale. (3rd June 2022) - Wang, Hexiang; Li, Yingxia; Xi, Qian; Han, Rongwei; Cullen, Patrick J; Du, Qijing; Yang, Yongxin; Forghani, Fereidoun; Zhang, Jiacheng; Wang, Jun
Abstract: The aim of this study was to examine the effectiveness of plasma-activated water (PAW) for inactivating Escherichia coli ( E. coli ) and retention of key quality factors for kale. Different plasma discharge times (1, 2, 3, 4, 5, and 10 min) and different exposure times (2, 4, 6, 8, 10, and 15 min) were used to investigate the inactivation effect of E. coli spot-inoculated on kale. The influence of different exposure times on the pH, hardness and color of kale was studied post-treatment. In addition, the effects of PAW on the shelf-life of kale over 12 d of storage at 4 °C were investigated. The results showed that after the treatment of 5-PAW-8 (8 min treatment by PAW generated by 5 min plasma discharge), the population of E. coli on kale was reduced by approximately 1.55 log colony-forming units (CFU)/g and the changes in pH, hardness and color of kale were not significant ( P >0.05). During the storage period after 5-PAW-8 treatment, the hardness, weight loss, color, surface morphology and ascorbic acid were found to be better than those of the two control groups ( P <0.05). Furthermore, no significant changes were observed in pH values, the content of total phenols, or 1, 1-dipheny1-2-picrylhydrazyl radical scavenging capacity ( P >0.05). It is indicated that PAW treatment is a promising method for improving microbiological safety and extending the shelf-life of kale.